The Interplay Between Respiratory Microbiota and Innate Immunity in Flavor E-Cigarette Vaping Induced Lung Dysfunction - Quinones Tavarez, Zahira; Li, Dongmei; Croft, Daniel P.; Gill, Steven R.; Ossip, Deborah J.; Rahman, Irfan (Frontiers in Microbiology, 2020)
Global usage of electronic nicotine delivery systems (ENDS) has been increasing in the last decade. ENDS are non-combustible tobacco products that heat and aerosolize a liquid containing humectants, with added flavorings and often nicotine. Though ENDS are promoted as a less harmful alternative to smoking, current evidence link their use to a wide range of deleterious health effects including acute and chronic lung damage. ENDS can elicit an inflammatory response and impair the innate immune response in the lungs. Exposure to ENDS flavorings results in abnormal activation of the lung epithelial cells and β-defensins, dysfunction of the macrophage phagocytic activity, increased levels of mucin (MUC5AC) and abnormal activation of the neutrophilic response (NETosis). ENDS menthol flavorings disrupt innate immunity and might be associated with allergies and asthma through activation of transient receptor potential ankyrin 1 (TRAP1). Recent studies have expanded our understanding of the relationship between the homeostasis of lung innate immunity and the immunomodulatory effect of the host-microbiota interaction. Alterations of the normal respiratory microbiota have been associated with chronic obstructive pulmonary disease (COPD), asthma, atopy and cystic fibrosis complications which are strongly associated with smoking and potentially with ENDS use. Little is known about the short- and long-term effects of ENDS on the respiratory microbiota, their impact on the innate immune response and their link to pulmonary health and disease. Here we discuss the associated innate-immune mechanisms in relation with microbiota in the pathogenesis of ENDS-induced lung dysfunction and identify future areas of research.